Analisis Perubahan Vegetasi dan Variabilitas Curah Hujan di Kawasan Taman Nasional Lore Lindu, Sulawesi Tengah - Wenas Ganda Kurnia; Rezfiko Agdialta (Buletin GAW Bariri, 2020)
Lore Lindu National Park is the major zone of the Lore Lindu Biosphere Reserve that is located in Central Sulawesi Province. The National Park consists mainly of mountain and sub-mountain forest (± 90%) and a small part of lowland forest (± 10%). Vegetation changes and climate variability in this ecological zone will have a wide impact on ecosystems from local to global levels. Climate anomalies that occur have the potential to cause changes in rainfall variability and vegetation changes. The purpose of this study is to analyze the correlation of Normalize Difference Vegetation Index (NDVI) with rainfall variability in Lore Lindu National Park use the Pearson correlation method. The data used are rainfall data from 2015 to 2017 from several rain posts around the Lore Lindu National Park area, and NDVI data was taken from NOAA satellites using Advanced Very High Resolution Radiometer (AVHRR) sensors. In this study for further analysis used data from two rainfall posts where the average of rainfall has the highest correlation with NDVI changes, namely Doda and Lore Peore rainfall posts. The results of this study show that rainfall is positively correlated to NDVI, which means that rainfall changes are followed by changes in NDVI (changes in vegetation). The highest correlation occurred in Doda rain post, this is due to the location of the Doda rain post which is close to dense vegetation in the Lore Lindu National Park area.